Nanomedicine-based Curcumin Approach Improved ROS Damage in Best Dystrophy-specific Induced Pluripotent Stem Cells. Issue 11 (November 2019) - Lin, Tai-Chi; Lin, Yi-Ying; Hsu, Chih-Chen; Yang, Yi-Ping; Yang, Chang-Hao; Hwang, De-Kuang; Wang, Chien-Ying; Liu, Yung-Yang; Lo, Wen-Liang; Chiou, Shih-Hwa; Peng, Chi-Hsien; Chen, Shih-Jen; et al.
Best dystrophy (BD), also termed best vitelliform macular dystrophy (BVMD), is a juvenile-onset form of macular degeneration and can cause central visual loss. Unfortunately, there is no clear definite therapy for BD or improving the visual function on this progressive disease. The human induced pluripotent stem cell (iPSC) system has been recently applied as an effective tool for genetic consultation and chemical drug screening. In this study, we developed patient-specific induced pluripotent stem cells (BD-iPSCs) from BD patient-derived dental pulp stromal cells and then differentiated BD-iPSCs into retinal pigment epithelial cells (BD-RPEs). BD-RPEs were used as an expandable platform for in vitro candidate drug screening. Compared with unaffected sibling-derived iPSC-derived RPE cells (Ctrl-RPEs), BD-RPEs exhibited typical RPE-specific markers with a lower expression of the tight junction protein ZO-1 and Bestrophin-1 (BEST1), as well as reduced phagocytic capabilities. Notably, among all candidate drugs, curcumin was the most effective for upregulating both the BEST1 and ZO-1 genes in BD-RPEs. Using the iPSC-based drug-screening platform, we further found that curcumin can significantly improve the mRNA expression levels of Best gene in BD-iPSC-derived RPEs. Importantly, we demonstrated that curcumin-loaded PLGA nanoparticles (Cur-NPs) were efficiently internalized by BD-RPEs. The Cur-NPs-based controlled release formulation further increased the expression of ZO-1 and Bestrophin-1, and promoted the function of phagocytosis and voltage-dependent calcium channels in BD-iPSC-derived RPEs. We further demonstrated that Cur-NPs enhanced the expression of antioxidant enzymes with a decrease in intracellular ROS production and hydrogen peroxide-induced oxidative stress. Collectively, these data supported that Cur-NPs provide a potential cytoprotective effect by regulating the anti-oxidative abilities of degenerated RPEs. In addition, the application of patient-specific iPSCs provides an effective platform for drug screening and personalized medicine in incurable diseases.